(untitled) (Pragya Darshan प्रज्ञा दर्शन, 2023)
We have developed a straightforward and uncomplicated technique for creating alkaline exchange membranes (AEMs) that possess both high alkaline durability and improved ionic conductivity. This method provides an appealing alternative to conventional approaches, notably by eliminating the need for the use of the carcinogenic reagent chloromethyl methyl ether, typically employed in AEM preparation. Examination of the membranes via scanning electron microscopy (SEM) reveals a consistently smooth surface. Augmenting the ion-exchange material’s weight percentage in the casting solution results in enhanced water content, ion exchange capacity, and electrical conductivity. Importantly, our approach entirely circumvents the use of the hazardous chloromethy l methyl ether reagent, commonly associated with AEM preparation. TGA for thermal stability and chemical stability, conductivity with impedance data, and electrochemical tests are going on. The outcomes of this study present an appealing alternative to traditional methods for AEM synthesis.